If it's not what You are looking for type in the equation solver your own equation and let us solve it.
20=4-4(t-2)
We move all terms to the left:
20-(4-4(t-2))=0
We calculate terms in parentheses: -(4-4(t-2)), so:We get rid of parentheses
4-4(t-2)
determiningTheFunctionDomain -4(t-2)+4
We multiply parentheses
-4t+8+4
We add all the numbers together, and all the variables
-4t+12
Back to the equation:
-(-4t+12)
4t-12+20=0
We add all the numbers together, and all the variables
4t+8=0
We move all terms containing t to the left, all other terms to the right
4t=-8
t=-8/4
t=-2
| (15)e+9=15+9 | | -a/10=4 | | -18=a-17 | | (13-4t)(13+4t)=0 | | 15/7x=9 | | -16.74=0.2b-3.3b | | v/5+2=-1 | | ,8v-4.9+7.7v=0.2 | | 8-(b-3)=b-9 | | 46+9a=-5a+7 | | 5+14x=9x-5. | | -5x-10=50x= | | -6=-4-4a+6 | | 15+z=2 | | 8(t-1)/4+8=12 | | b/7-2/3=13/15 | | x^2+20x=2250 | | 3=7r-8r | | 3x=-×+-12 | | 10x-77=7x | | -20x=-6 | | 7x+36=10x+24 | | 2x²+5/3x+6=0 | | 1+2x-3=6 | | (5x-2)-4x=16 | | 96-4b+3b=16 | | -14=b-2-7b | | -7x-34=-4x+29 | | p^2-4p+4=p | | -12=-1+x-5 | | 50-7x=2x-13 | | (-12)+(-4x)+2=4x+12 |